Efectividad del ketoprofeno y metamizol en la analgesia postoperatoria inmediata en colecistectomías laparoscópicas - Morillo Zavaleta, Guillermo José Fernando (2017)
Prospective, observational and analytical study carried out between July 2015 and December 2015 at the Trujillo Regional Teaching Hospital in 72 people aged between 18 and 59 years operated in the operating room of the hospital and with the objective of determining if ketoprofen is More effective than metamizole in immediate postoperative analgesia in laparoscopic cholecystectomized patients. The results obtained were that a highly significant statistical difference was found in the postoperative analgesic effectiveness in laparoscopic cholecystectomized patients of ketoprofen with respect to metamizole (p = 0.0000) at EVA 0. We also found a statistically significant difference in postoperative analgesic effectiveness However, we found a statistically non-significant difference in the postoperative analgesic effectiveness in cholecystectomized patients with ketoprofen compared to metamizole (p = 0.2633) to EVA in patients who underwent laparoscopic ketoprofen compared to metamizole (p = 0.0127) 60. It was concluded that ketoprofen is more effective than metamizole in immediate postoperative analgesia in laparoscopic cholecystectomized patients at EVA0, EVA 30 but not at EVA at the postoperative hour in which both had the same analgesic effectiveness